(a) Construction of the formula : We will use Hermite
interpolation at the n n n zeros of ϕ n \phi_n ϕ n to construct the quadrature
rule. The interpolant is given by, see Section 6.8.2
H n ( x ) = ∑ j = 1 n f ( x j ) h j ( x ) + ∑ j = 1 n f ′ ( x j ) h ~ j ( x ) ∈ P 2 n − 1 H_n(x) = \sum_{j=1}^n f(x_j) h_j(x) + \sum_{j=1}^n f'(x_j) \tilde{h}_j(x) \in \poly_{2n-1} H n ( x ) = j = 1 ∑ n f ( x j ) h j ( x ) + j = 1 ∑ n f ′ ( x j ) h ~ j ( x ) ∈ P 2 n − 1 where
h j ( x ) = [ 1 − 2 ℓ j ′ ( x j ) ( x − x j ) ] [ ℓ j ( x ) ] 2 , h ~ j ( x ) = ( x − x j ) [ ℓ j ( x ) ] 2 ℓ j ( x ) = ∏ i = 1 , i ≠ j n x − x i x j − x i \begin{gather}
h_j(x) = [1 - 2\ell_j'(x_j)(x-x_j)] [\ell_j(x)]^2, \qquad \tilde{h}_j(x) = (x-x_j) [\ell_j(x)]^2 \\
\ell_j(x) = \prod_{i=1,i\ne j}^n \frac{x-x_i}{x_j - x_i}
\end{gather} h j ( x ) = [ 1 − 2 ℓ j ′ ( x j ) ( x − x j )] [ ℓ j ( x ) ] 2 , h ~ j ( x ) = ( x − x j ) [ ℓ j ( x ) ] 2 ℓ j ( x ) = i = 1 , i = j ∏ n x j − x i x − x i The Hermite interpolation error is
e n ( x ) = f ( x ) − H n ( x ) = [ ψ n ( x ) ] 2 f [ x 1 , x 1 , … , x n , x n , x ] = [ ψ n ( x ) ] 2 ( 2 n ) ! f ( 2 n ) ( η ) , η ∈ [ a , b ] \begin{align*}
e_n(x)
&= f(x) - H_n(x) \\
&= [\psi_n(x)]^2 f[x_1,x_1,\ldots,x_n,x_n,x] \\
&= \frac{[\psi_n(x)]^2}{(2n)!} f^{(2n)}(\eta), \quad \eta \in [a,b]
\end{align*} e n ( x ) = f ( x ) − H n ( x ) = [ ψ n ( x ) ] 2 f [ x 1 , x 1 , … , x n , x n , x ] = ( 2 n )! [ ψ n ( x ) ] 2 f ( 2 n ) ( η ) , η ∈ [ a , b ] where
ψ n ( x ) = ( x − x 1 ) … ( x − x n ) = 1 A n ϕ n ( x ) \psi_n(x) = (x-x_1)\ldots(x-x_n) = \frac{1}{A_n} \phi_n(x) ψ n ( x ) = ( x − x 1 ) … ( x − x n ) = A n 1 ϕ n ( x ) Now
∫ a b w ( x ) f ( x ) d x = ∫ a b w ( x ) H n ( x ) d x + ∫ a n w ( x ) e n ( x ) d x = : I n ( f ) + E n ( f ) \begin{align}
\int_a^b w(x) f(x) \ud x
&= \int_a^b w(x) H_n(x) \ud x + \int_a^n w(x) e_n(x) \ud x \\
&=: I_n(f) + E_n(f)
\end{align} ∫ a b w ( x ) f ( x ) d x = ∫ a b w ( x ) H n ( x ) d x + ∫ a n w ( x ) e n ( x ) d x =: I n ( f ) + E n ( f ) The degree of precision of I n I_n I n is atleast 2 n − 1 2n-1 2 n − 1 since H n H_n H n is exact
for such polynomials. Moreover, for f ( x ) = x 2 n f(x) = x^{2n} f ( x ) = x 2 n ,
E n ( x 2 n ) = ∫ a b w ( x ) e n ( x ) d x = ∫ a b w ( x ) [ ψ n ( x ) ] 2 ( 2 n ) ! f ( 2 n ) ( η ) d x = ∫ a b w ( x ) [ ψ n ( x ) ] 2 ( 2 n ) ! ( 2 n ) ! d x = ∫ a b w ( x ) [ ψ n ( x ) ] 2 d x > 0 \begin{aligned}
E_n(x^{2n})
&= \int_a^b w(x) e_n(x) \ud x \\
&= \int_a^b w(x) \frac{[\psi_n(x)]^2}{(2n)!} f^{(2n)}(\eta) \ud x \\
&= \int_a^b w(x) \frac{[\psi_n(x)]^2}{(2n)!} (2n)! \ud x \\
&= \int_a^b w(x) [\psi_n(x)]^2 \ud x > 0
\end{aligned} E n ( x 2 n ) = ∫ a b w ( x ) e n ( x ) d x = ∫ a b w ( x ) ( 2 n )! [ ψ n ( x ) ] 2 f ( 2 n ) ( η ) d x = ∫ a b w ( x ) ( 2 n )! [ ψ n ( x ) ] 2 ( 2 n )! d x = ∫ a b w ( x ) [ ψ n ( x ) ] 2 d x > 0 Hence the degree of precision of I n I_n I n is exactly 2 n − 1 2n-1 2 n − 1 .
(b) Simpler formula for I n ( f ) I_n(f) I n ( f ) : The integration formula is
I n ( f ) = ∑ j = 1 n f ( x j ) ∫ a b w ( x ) h j ( x ) d x + ∑ j = 1 n f ′ ( x j ) ∫ a b w ( x ) h ~ j ( x ) d x I_n(f) = \sum_{j=1}^n f(x_j) \int_a^b w(x) h_j(x) \ud x + \sum_{j=1}^n f'(x_j) \int_a^b w(x) \tilde{h}_j(x) \ud x I n ( f ) = j = 1 ∑ n f ( x j ) ∫ a b w ( x ) h j ( x ) d x + j = 1 ∑ n f ′ ( x j ) ∫ a b w ( x ) h ~ j ( x ) d x Since, see Section 6.3.1
ℓ j ( x ) = ψ n ( x ) ( x − x j ) ψ n ′ ( x j ) = ϕ n ( x ) ( x − x j ) ϕ n ′ ( x j ) ⟹ h ~ j ( x ) = ( x − x j ) ℓ j ( x ) ⋅ ℓ j ( x ) = ϕ n ( x ) ϕ n ′ ( x j ) ⋅ ℓ j ( x ) \begin{gather}
\ell_j(x) = \frac{\psi_n(x)}{(x-x_j) \psi_n'(x_j)} = \frac{\phi_n(x)}{(x-x_j) \phi_n'(x_j)} \\
\implies \tilde{h}_j(x) = (x-x_j) \ell_j(x) \cdot \ell_j(x) = \frac{\phi_n(x)}{\phi_n'(x_j)} \cdot \ell_j(x)
\end{gather} ℓ j ( x ) = ( x − x j ) ψ n ′ ( x j ) ψ n ( x ) = ( x − x j ) ϕ n ′ ( x j ) ϕ n ( x ) ⟹ h ~ j ( x ) = ( x − x j ) ℓ j ( x ) ⋅ ℓ j ( x ) = ϕ n ′ ( x j ) ϕ n ( x ) ⋅ ℓ j ( x ) Hence
∫ a b w ( x ) h ~ j ( x ) d x = 1 ϕ n ′ ( x j ) ∫ a b w ( x ) ϕ n ( x ) ℓ j ( x ) d x = 0 , j = 1 , 2 , … , n \int_a^b w(x) \tilde{h}_j(x) \ud x = \frac{1}{\phi_n'(x_j)}\int_a^b w(x) \phi_n(x) \ell_j(x) \ud x = 0, \qquad j=1,2,\ldots,n ∫ a b w ( x ) h ~ j ( x ) d x = ϕ n ′ ( x j ) 1 ∫ a b w ( x ) ϕ n ( x ) ℓ j ( x ) d x = 0 , j = 1 , 2 , … , n since degree( ℓ j ) = n − 1 (\ell_j) = n-1 ( ℓ j ) = n − 1 and ϕ n \phi_n ϕ n is orthogonal to all polynomials of degree < n < n < n . Hence
I n ( f ) = ∑ j = 1 n w j f ( x j ) , w j = ∫ a b w ( x ) h j ( x ) d x I_n(f) = \sum_{j=1}^n w_j f(x_j), \qquad w_j = \int_a^b w(x) h_j(x) \ud x I n ( f ) = j = 1 ∑ n w j f ( x j ) , w j = ∫ a b w ( x ) h j ( x ) d x We do not need to know the derivatives f ′ ( x j ) f'(x_j) f ′ ( x j ) !!!
(c) Uniqueness of I n ( f ) I_n(f) I n ( f ) : Suppose we have another numerical integration formula
∫ a b w ( x ) f ( x ) d x ≈ ∑ j = 1 n v j f ( z j ) \int_a^b w(x) f(x) \ud x \approx \sum_{j=1}^n v_j f(z_j) ∫ a b w ( x ) f ( x ) d x ≈ j = 1 ∑ n v j f ( z j ) that has degree of precision ≥ 2 n − 1 \ge 2n-1 ≥ 2 n − 1 . For any p ∈ P 2 n − 1 p \in \poly_{2n-1} p ∈ P 2 n − 1 , the Hermite interpolant using nodes { z j } \{ z_j \} { z j } is exact and
p ( x ) = ∑ j = 1 n p ( z j ) g j ( x ) + ∑ j = 1 n p ′ ( z j ) g ~ j ( x ) p(x) = \sum_{j=1}^n p(z_j) g_j(x) + \sum_{j=1}^n p'(z_j) \tilde{g}_j(x) p ( x ) = j = 1 ∑ n p ( z j ) g j ( x ) + j = 1 ∑ n p ′ ( z j ) g ~ j ( x ) where
g j ( x ) = [ 1 − 2 ( x − z j ) ℓ ˉ j ( z j ) ] [ ℓ ˉ j ( x ) ] 2 g ~ j ( x ) = ( x − z j ) [ ℓ ˉ j ( x ) ] 2 = ℓ ˉ j ( x ) χ n ( x ) χ n ′ ( z j ) ℓ ˉ j ( x ) = ∏ i = 1 , i ≠ j n x − z i z j − z i , χ n ( x ) = ( x − z 1 ) … ( x − z n ) \begin{gather}
g_j(x) = [ 1 - 2 (x - z_j) \bar{\ell}_j (z_j) ] [\bar{\ell}_j(x)]^2 \\
\tilde{g}_j(x) = (x-z_j) [\bar{\ell}_j(x)]^2 = \frac{\bar{\ell}_j(x) \chi_n(x)}{\chi_n'(z_j)} \\
\bar{\ell}_j(x) = \prod_{i=1,i \ne j}^n \frac{x-z_i}{z_j - z_i}, \qquad \chi_n(x) = (x-z_1)\ldots(x-z_n)
\end{gather} g j ( x ) = [ 1 − 2 ( x − z j ) ℓ ˉ j ( z j )] [ ℓ ˉ j ( x ) ] 2 g ~ j ( x ) = ( x − z j ) [ ℓ ˉ j ( x ) ] 2 = χ n ′ ( z j ) ℓ ˉ j ( x ) χ n ( x ) ℓ ˉ j ( x ) = i = 1 , i = j ∏ n z j − z i x − z i , χ n ( x ) = ( x − z 1 ) … ( x − z n ) Since the quadrature formula is exact for p ∈ P 2 n − 1 p \in \poly_{2n-1} p ∈ P 2 n − 1
∑ j = 1 n v j p ( z j ) = ∫ a b w ( x ) p ( x ) d x = ∑ j = 1 n p ( z j ) ∫ a b w ( x ) g j ( x ) d x + ∑ j = 1 n p ′ ( z j ) ∫ a b w ( x ) g ~ j ( x ) d x \begin{align*}
\sum_{j=1}^n v_j p(z_j)
&= \int_a^b w(x) p(x) \ud x \\
&= \sum_{j=1}^n p(z_j) \int_a^b w(x) g_j(x) \ud x + \sum_{j=1}^n p'(z_j) \int_a^b w(x) \tilde{g}_j(x) \ud x
\end{align*} j = 1 ∑ n v j p ( z j ) = ∫ a b w ( x ) p ( x ) d x = j = 1 ∑ n p ( z j ) ∫ a b w ( x ) g j ( x ) d x + j = 1 ∑ n p ′ ( z j ) ∫ a b w ( x ) g ~ j ( x ) d x Take p ( x ) = g ~ i ( x ) p(x) = \tilde{g}_i(x) p ( x ) = g ~ i ( x ) . Note that
g ~ i ( z j ) = 0 , g ~ i ′ ( z j ) = δ i j \tilde{g}_i(z_j) = 0, \qquad \tilde{g}_i'(z_j) = \delta_{ij} g ~ i ( z j ) = 0 , g ~ i ′ ( z j ) = δ ij Hence we get
0 = 0 + g ~ i ′ ( z i ) ∫ a b w ( x ) g ~ i ( x ) d x 0 = 0 + \tilde{g}_i'(z_i) \int_a^b w(x) \tilde{g}_i(x) \ud x 0 = 0 + g ~ i ′ ( z i ) ∫ a b w ( x ) g ~ i ( x ) d x ⟹ ∫ a b w ( x ) g ~ i ( x ) d x = 1 χ n ′ ( z i ) ∫ a b w ( x ) χ n ( x ) ℓ ˉ i ( x ) d x = 0 , i = 1 , 2 , … , n \implies \int_a^b w(x) \tilde{g}_i(x) \ud x = \frac{1}{\chi_n'(z_i)} \int_a^b w(x) \chi_n(x) \bar{\ell}_i(x) \ud x = 0, \qquad i=1,2,\ldots,n ⟹ ∫ a b w ( x ) g ~ i ( x ) d x = χ n ′ ( z i ) 1 ∫ a b w ( x ) χ n ( x ) ℓ ˉ i ( x ) d x = 0 , i = 1 , 2 , … , n Since degree( ℓ ˉ i ) = n − 1 (\bar{\ell}_i)=n-1 ( ℓ ˉ i ) = n − 1 and they form a basis for P n − 1 \poly_{n-1} P n − 1 , we get
∫ a b w ( x ) χ n ( x ) p ( x ) = 0 , ∀ p ∈ P n − 1 \int_a^b w(x) \chi_n(x) p(x) = 0, \qquad \forall p \in \poly_{n-1} ∫ a b w ( x ) χ n ( x ) p ( x ) = 0 , ∀ p ∈ P n − 1 Hence χ n \chi_n χ n is orthogonal to P n − 1 = span ( ϕ 0 , ϕ 1 , … , ϕ n − 1 ) \poly_{n-1} = \textrm{span}(\phi_0,\phi_1, \ldots,\phi_{n-1}) P n − 1 = span ( ϕ 0 , ϕ 1 , … , ϕ n − 1 ) and note that χ n ∈ P n \chi_n \in \poly_n χ n ∈ P n . But orthogonal polynomials are unique upto a multiplicative constant. Hence χ n ( x ) = c ϕ n ( x ) \chi_n(x) = c \phi_n(x) χ n ( x ) = c ϕ n ( x ) and in particular their zeros are same, which imples that z j = x j z_j = x_j z j = x j . Moreover, since degree( h i ) = 2 n − 1 (h_i)=2n-1 ( h i ) = 2 n − 1
w i = ∫ a b w ( x ) h i ( x ) d x = ∑ j = 1 n v j h i ( x j ) ⏟ δ i j = v i w_i = \int_a^b w(x) h_i(x)\ud x = \sum_{j=1}^n v_j \underbrace{h_i(x_j)}_{\delta_{ij}} = v_i w i = ∫ a b w ( x ) h i ( x ) d x = j = 1 ∑ n v j δ ij h i ( x j ) = v i (d) Weights are positive :
w i = ∫ a b w ( x ) h i ( x ) d x = ∫ a b w ( x ) [ 1 − 2 ℓ i ′ ( x i ) ( x − x i ) ] [ ℓ i ( x ) ] 2 d x = ∫ a b w ( x ) [ ℓ i ( x ) ] 2 d x − 2 ℓ i ′ ( x i ) ∫ a b w ( x ) h ~ i ( x ) d x ⏟ = 0 = ∫ a b w ( x ) [ ℓ i ( x ) ] 2 d x > 0 \begin{aligned}
w_i &= \int_a^b w(x) h_i(x) \ud x \\
&= \int_a^b w(x) [1 - 2 \ell_i'(x_i)(x-x_i)] [\ell_i(x)]^2 \ud x \\
&= \int_a^b w(x) [\ell_i(x)]^2 \ud x - 2 \ell_i'(x_i) \underbrace{\int_a^b w(x) \tilde{h}_i(x) \ud x}_{=0} \\
&= \int_a^b w(x) [\ell_i(x)]^2 \ud x > 0
\end{aligned} w i = ∫ a b w ( x ) h i ( x ) d x = ∫ a b w ( x ) [ 1 − 2 ℓ i ′ ( x i ) ( x − x i )] [ ℓ i ( x ) ] 2 d x = ∫ a b w ( x ) [ ℓ i ( x ) ] 2 d x − 2 ℓ i ′ ( x i ) = 0 ∫ a b w ( x ) h ~ i ( x ) d x = ∫ a b w ( x ) [ ℓ i ( x ) ] 2 d x > 0 (e) Error formula : Assume that f ∈ C 2 n [ a , b ] f \in \cts^{2n}[a,b] f ∈ C 2 n [ a , b ] . Then the integration error is
E n ( f ) = ∫ a b w ( x ) e n ( x ) d x = ∫ a b w ( x ) [ ψ n ( x ) ] 2 f [ x 1 , x 1 , … , x n , x n , x ] d x = f [ x 1 , x 1 , … , x n , x n , ξ ] ∫ a b w ( x ) [ ψ n ( x ) ] 2 d x , ξ ∈ [ a , b ] = f ( 2 n ) ( η ) ( 2 n ) ! 1 A n 2 ∫ a b w ( x ) [ ϕ n ( x ) ] 2 d x = f ( 2 n ) ( η ) ( 2 n ) ! 1 A n 2 γ n \begin{aligned}
E_n(f)
&= \int_a^b w(x) e_n(x) \ud x \\
&= \int_a^b w(x) [\psi_n(x)]^2 f[x_1,x_1,\ldots,x_n,x_n,x] \ud x \\
&= f[x_1,x_1,\ldots,x_n,x_n,\xi] \int_a^b w(x) [\psi_n(x)]^2 \ud x, \quad \xi\in[a,b] \\
&= \frac{f^{(2n)}(\eta)}{(2n)!} \frac{1}{A_n^2} \int_a^b w(x) [\phi_n(x)]^2 \ud x \\
&= \frac{f^{(2n)}(\eta)}{(2n)!} \frac{1}{A_n^2} \gamma_n
\end{aligned} E n ( f ) = ∫ a b w ( x ) e n ( x ) d x = ∫ a b w ( x ) [ ψ n ( x ) ] 2 f [ x 1 , x 1 , … , x n , x n , x ] d x = f [ x 1 , x 1 , … , x n , x n , ξ ] ∫ a b w ( x ) [ ψ n ( x ) ] 2 d x , ξ ∈ [ a , b ] = ( 2 n )! f ( 2 n ) ( η ) A n 2 1 ∫ a b w ( x ) [ ϕ n ( x ) ] 2 d x = ( 2 n )! f ( 2 n ) ( η ) A n 2 1 γ n (f) Formula for the weights : We have already shown that the weights are positive. To obtain a simpler formula, take f ( x ) = ℓ i ( x ) f(x) = \ell_i(x) f ( x ) = ℓ i ( x ) and note that degree(ℓ i ) = n − 1 \ell_i)=n-1 ℓ i ) = n − 1 , it can be exactly integrated
∫ a b w ( x ) ℓ i ( x ) d x = ∑ j = 1 n w j ℓ i ( x j ) + E n ( ℓ i ) = w i + 0 \int_a^b w(x) \ell_i(x) \ud x = \sum_{j=1}^n w_j \ell_i(x_j) + E_n(\ell_i) = w_i + 0 ∫ a b w ( x ) ℓ i ( x ) d x = j = 1 ∑ n w j ℓ i ( x j ) + E n ( ℓ i ) = w i + 0 Hence (this was also shown in Section 8.8.2 )
w i = ∫ a b w ( x ) ℓ i ( x ) d x = 1 ϕ n ′ ( x i ) ∫ a b w ( x ) ϕ n ( x ) ( x − x i ) d x w_i = \int_a^b w(x) \ell_i(x) \ud x = \frac{1}{\phi_n'(x_i)} \int_a^b \frac{w(x) \phi_n(x)}{(x-x_i)} \ud x w i = ∫ a b w ( x ) ℓ i ( x ) d x = ϕ n ′ ( x i ) 1 ∫ a b ( x − x i ) w ( x ) ϕ n ( x ) d x Recall the Christoffel-Darboux identity from Section 8.9.3
∑ k = 0 n ϕ k ( x ) ϕ k ( y ) γ k = ϕ n + 1 ( x ) ϕ n ( y ) − ϕ n ( x ) ϕ n + 1 ( y ) a n γ n ( x − y ) , x ≠ y \sum_{k=0}^n \frac{\phi_k(x) \phi_k(y)}{\gamma_k} = \frac{\phi_{n+1}(x) \phi_n(y) - \phi_n(x) \phi_{n+1}(y)}{a_n \gamma_n (x-y)}, \qquad x \ne y k = 0 ∑ n γ k ϕ k ( x ) ϕ k ( y ) = a n γ n ( x − y ) ϕ n + 1 ( x ) ϕ n ( y ) − ϕ n ( x ) ϕ n + 1 ( y ) , x = y Take y = x i y = x_i y = x i and use ϕ n ( y ) = ϕ n ( x i ) = 0 \phi_n(y)=\phi_n(x_i)=0 ϕ n ( y ) = ϕ n ( x i ) = 0
∑ k = 0 n − 1 ϕ k ( x ) ϕ k ( x i ) γ k = − ϕ n ( x ) ϕ n + 1 ( x i ) a n γ n ( x − x i ) \sum_{k=0}^{n-1} \frac{\phi_k(x) \phi_k(x_i)}{\gamma_k} = -\frac{\phi_n(x) \phi_{n+1}(x_i)}{a_n \gamma_n (x-x_i)} k = 0 ∑ n − 1 γ k ϕ k ( x ) ϕ k ( x i ) = − a n γ n ( x − x i ) ϕ n ( x ) ϕ n + 1 ( x i ) Multiply by w ( x ) w(x) w ( x ) and integrate both sides; by orthogonality of { ϕ k } \{ \phi_k \} { ϕ k }
∫ a b w ( x ) ϕ k ( x ) d x = 0 , k ≥ 1 \int_a^b w(x) \phi_k(x) \ud x = 0, \qquad k \ge 1 ∫ a b w ( x ) ϕ k ( x ) d x = 0 , k ≥ 1 only the term k = 0 k=0 k = 0 in the sum survives, and since ϕ 0 ( x ) = \phi_0(x)= ϕ 0 ( x ) = constant, we get
1 γ 0 ∫ a b w ( x ) ϕ 0 ( x ) ϕ 0 ( x i ) d x = 1 = − ϕ n + 1 ( x i ) a n γ n ∫ a b w ( x ) ϕ n ( x ) x − x i d x = − ϕ n + 1 ( x i ) a n γ n w i ϕ n ′ ( x i ) \begin{align}
\frac{1}{\gamma_0} \int_a^b w(x) \phi_0(x)\phi_0(x_i)\ud x = 1 &= - \frac{\phi_{n+1}(x_i)}{a_n \gamma_n} \int_a^b \frac{w(x) \phi_n(x)}{x-x_i} \ud x\\
&= - \frac{\phi_{n+1}(x_i)}{a_n \gamma_n} w_i \phi_n'(x_i)
\end{align} γ 0 1 ∫ a b w ( x ) ϕ 0 ( x ) ϕ 0 ( x i ) d x = 1 = − a n γ n ϕ n + 1 ( x i ) ∫ a b x − x i w ( x ) ϕ n ( x ) d x = − a n γ n ϕ n + 1 ( x i ) w i ϕ n ′ ( x i ) which proves the formula for the weights.